2020
DOI: 10.1186/s13613-020-00772-7
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption therapy in critically ill with septic shock and acute kidney injury: a retrospective and prospective cohort study

Abstract: Background Haemoadsorption has been described as an effective way to control increased pro- and anti-inflammatory mediators (“cytokine storm”) in septic shock patients. No prospective or randomised clinical study has yet confirmed these results. However, no study has yet prospectively specifically investigated patients in severe septic shock with sepsis-associated acute kidney injury (SA-AKI). Therefore, we aimed to examine whether haemoadsorption could influence intensive care unit (ICU) and hospital mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Out of the 163 clinical articles available in PubMed, 58 were identified that mentioned "catecholamines and/or vasopressors". In total, 25 papers were excluded; 12 because of non-comparability of the measurement scales [25][26][27][28][29][30][31][32][33][34][35][36]; 4 because the type and dose of vasopressors were not specified [37][38][39][40]; 1 that reported combined norepinephrine and epinephrine doses [41]; 1 that only reported on patients that had survived [42]; and 7 where there were no measurements pre-and post-adsorber use in the same patient [43][44][45][46][47][48][49]. The remaining 33 articles were summarized without considering different study designs or duration of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 163 clinical articles available in PubMed, 58 were identified that mentioned "catecholamines and/or vasopressors". In total, 25 papers were excluded; 12 because of non-comparability of the measurement scales [25][26][27][28][29][30][31][32][33][34][35][36]; 4 because the type and dose of vasopressors were not specified [37][38][39][40]; 1 that reported combined norepinephrine and epinephrine doses [41]; 1 that only reported on patients that had survived [42]; and 7 where there were no measurements pre-and post-adsorber use in the same patient [43][44][45][46][47][48][49]. The remaining 33 articles were summarized without considering different study designs or duration of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The principle of cytokine adsorption is a promising technique to mitigate cytokine storm in critically ill patients [20]. However, there are only limited prospective data with control groups available that investigate the elimination of cytokines using CS [21][22][23]. Although a decrease in cytokines was described by different authors [15,24], this could be due to causal therapy approaches such as anti-infective or supportive therapy [25].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, few published studies focused on SA-AKI and renal outcome in septic patients who have received hemadsorption with CytoSorb, and none of them included pediatric patients ( 22 ). Therefore, the aim of this retrospective study was to evaluate the clinical and renal outcome after CytoSorb in association to CKRT in pediatric patients with sepsis or septic shock admitted to PICU.…”
Section: Introductionmentioning
confidence: 99%